2010
DOI: 10.4088/jcp.10m06018blu
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Efficacy and Safety of Desvenlafaxine in a Randomized, Placebo-Controlled Study of Perimenopausal and Postmenopausal Women With Major Depressive Disorder

Abstract: clinicaltrials.gov Identifier: NCT00369343.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Only desvenlafaxine has been specifically evaluated through randomized, placebo-controlled trials for antidepressant efficacy in peri-and postmenopausal depressed women; the 2 trials found that desvenlafaxine (50 mg daily, N ¼ 434 91 ; 100 mg and 200 mg daily, N ¼ 387 92 ) was superior to placebo. Importantly, a post-hoc analysis of these RCTs showed no differences in treatment response to desvenlafaxine between peri-and postmenopausal women.…”
Section: Is Antidepressant Medication Effective During Menopause?mentioning
confidence: 99%
“…Only desvenlafaxine has been specifically evaluated through randomized, placebo-controlled trials for antidepressant efficacy in peri-and postmenopausal depressed women; the 2 trials found that desvenlafaxine (50 mg daily, N ¼ 434 91 ; 100 mg and 200 mg daily, N ¼ 387 92 ) was superior to placebo. Importantly, a post-hoc analysis of these RCTs showed no differences in treatment response to desvenlafaxine between peri-and postmenopausal women.…”
Section: Is Antidepressant Medication Effective During Menopause?mentioning
confidence: 99%
“…Antidepressants remain the first line pharmacological treatment for depression in peri- and postmenopausal women. Only desvenlafaxine has been studied sufficiently and proven efficacious for peri- and postmenopausal depression in two large RCTs (Clayton, 2013; Kornstein, 2010). However, there are also small open label studies that suggest efficacy for SSRIs, SNRIs and vortioxetine (Maki et al, 2019).…”
Section: Complex Presentations and Special Populationsmentioning
confidence: 99%
“…Most other antidepressants have been trialled in cohorts of younger premenopausal or older postmenopausal women. 38,39 Clinical trials have shown that compared to placebo, antidepressants can help to reduce the frequency of VMS 40,41 ; however, compared to HRT they are much less effective. HRT has been shown to reduce the severity and frequency of VMS by up to 83%, whereas antidepressants reduced the severity by up to 50%.…”
Section: Treatmentmentioning
confidence: 99%